The heritage product as suggested by a marketing approach - Šola, Tomislav (Array, 2011)
The paper aims to present heritage and museums in relation to marketing and product oriented activities of today's world. The conclusion is that the product is the difference in the visitors between their state before and after the visit and museums becoming making museums the main driving force in social and cultural development.